Performance Assessment of a Solar Assisted Ground Source Heat Pump in a Mountain Site. (November 2015) - Fabrizio, Enrico; Ferrara, Maria; Urone, Giampiero; Corgnati, Stefano P.; Pronsati, Simone; Filippi, Marco
Abstract: Systems based on the integrated use of multiple renewable energy sources, such as "Solar Assisted Geothermal Heat Pumps" (SAGHPs), seem to increase efficiency and overcome limits of the use of traditional heat pump systems. In this work, a SAGHP providing energy for heating and DHW of a newly built restaurant in an Alpine ski park was analyzed through transient simulations with TRNSYS®, following the collection of information about the system component, the operation and the weather conditions of the mountain site. The annual energy balance allowed different system operation modes to be compared.